Validation of the French version of the Body Awareness Questionnaire: toward a way to assess alexisomia - Carre, Arnaud; Shankland, Rebecca; Guillaume, Philippe; Duclos, Jeanne; El-Jor, Claire; Pellissier, Sonia; Flaudias, Valentin (Frontiers in Psychology, 2024)
Background Awareness of one's own states is a particularly important part of cognition and emotion regulation. Recently, the concept of alexisomia has been used to refer to lack of awareness and expression of somatic sensations. Developing self-reported questionnaires to evaluate alexisomia represents a challenge for clinical psychology and medicine. In this context, we suggested to adapt the Body Awareness Questionnaire in French to measure alexisomia and its relation to alexithymia. In fact, we carried out a backtranslation and studied the validity of the construct in relation to proximal constructs around emotional awareness. Methods For this study, 610 university students completed questionnaires measuring a three dimensions alexithymia concept [with The Toronto Alexithymia Scale (TAS-20)] or the five dimensions alexithymia concept [with The Bermond-Vorts Alexithymia Questionnaire (BVAQ-B)] and alexisomia (with the BAQ). Results Confirmatory factor analyses showed that the BAQ can be envisaged through 4 factors as well as a unidimensional model to refer to alexisomia. We also found that body awareness was negatively related to scores of alexithymia. Conclusion Results are discussed in light of the construct of alexisomia and its clinical implications in somatic as well as mental disorders. We suggest that the BAQ, which assesses interoception, can contribute, in part, to the assessment of alexisomia. Like alexithymia, this is a key concept to take into consideration when designing treatment and prevention programs.